The Experience of the International Islamic University in Digital Media Education - Altabaa, Homam; Iskandar, Iylia Marsya; Al-Hidabi, Dawood; Hamawiya, Adham (IIUM Journal of Educational Studies, 2023)
The IIUMToday platform is the main source of news for the International Islamic University Malaysia (IIUM). It has been managed and published by university students since its establishment in early May 2014, under the supervision of the Department of Communication at the Abdul Hamid Abu Sulaiman Kulliyyah of Islamic Revealed Knowledge and Human Sciences. The aim of this research was to analyse the platform’s experience to assess the success of media students in developing their skills to meet the requirements of the media industry in general, and digital media in particular. The research employed a qualitative approach and utilized thematic analysis of in-depth interviews conducted with a purposive sample of members affiliated with the IIUMToday platform. Among the most prominent findings of the research is that university media is an important element that should be rooted in the teaching curricula of media departments, in order to ensure that students obtain sufficient practical experience other than compulsory training.